Rapid progression to Richter’s syndrome in a patient with chronic lymphocytic leukemia and near-triploid karyotype - Denčić-Fekete, Marija; Terzić, Tatjana; Jaković, Ljubomir; Djurašinović, Vladislava; Karan Djurašević, Teodora; Radojković, Milica; Pavlović, Sonja; Bogdanović, Andrija (Vojnosanitetski pregled, 2023)
Introduction. The presence of aneuploidy in patients diagnosed with chronic lymphocytic leukemia (CLL), except trisomy 12, is considered quite uncommon. Hyperdiploidy or near-tetraploidy (occurring in 1–3% of all CLL patients) usually confer a poor prognosis. Case report. We report a patient in a progressive phase of CLL with near–triploid karyotype. The prognosis of the disease was more precisely determined by applying the cytogenetic analysis of the karyotype and was complemented with molecular methods and pathohistological examination. The complex karyotype was accompanied by the TP53, C-MYC, and IGH gene disruptions, the most probable cause of rapid evolution into Richter’s syndrome. Conclusion. The use of comprehensive contemporary diagnostic techniques is highly recommended in patients who are in the progressive phase of CLL, primarily for the adequate choice of management strategy. The presented case confirms that aneuploidy in CLL patients indicates poor prognosis, which is in accordance with previous publications reporting on cases of CLL patients with aneuploidy.